Tremella fuciformis polysaccharide reduces obesity in high-fat diet-fed mice by modulation of gut microbiota - He, Gang; Chen, Tangcong; Huang, Lifen; Zhang, Yiyuan; Feng, Yanjiao; Qu, Shaokui; Yin, Xiaojing; Liang, Li; Yan, Jun; Liu, Wei (Frontiers in Microbiology, 2022)
Obesity is a metabolic disease associated with gut microbiota and low-grade chronic inflammation. Tremella fuciformis is a medicinal and edible fungus; polysaccharide (TP) is the main active component, which has a variety of biological activities, such as hypoglycemic and hypolipidemic. However, the anti-obesity effects and potential mechanisms of TP have never been reported. This study was conducted to elucidate the inhibitory effect of TP on high-fat diet (HFD)-induced obesity in mice. Mice were split into five groups: normal chow diet (NCD) group, NCD_TP_H group, HFD group, HFD_TP_L group and HFD_TP_H group. Our study showed that TP inhibited high-fat diet-induced weight gain and fat accumulation in mice and reduced blood glucose, hyperlipidemia and inflammation. TP also improved gut microbiota disorders by reducing the Firmicutes/Bacteroidetes ratio and modulating the relative abundance of specific gut microbiota. We also found that the anti-obesity and gut microbiota-modulating effects of TP could be transferred to HFD-fed mice via faecal microbiota transplantation (FMT), confirming that the gut microbiota was one of the targets of TP for obesity inhibition. Further studies showed that TP increased the production of short-chain fatty acids and the secretion of intestinal hormones. Our studies showed that TP inhibited obesity by modulating inflammation and the microbe-gut-brain axis, providing a rationale for developing TP to treat obesity and its complications.